Conducting Polymer‐ECM Scaffolds for Human Neuronal Cell Differentiation. Issue 20 (17th August 2022) - Barberio, Chiara; Saez, Janire; Withers, Aimee; Nair, Malavika; Tamagnini, Francesco; Owens, Roisin M.
Abstract: 3D cell culture formats more closely resemble tissue architecture complexity than 2D systems, which are lacking most of the cell–cell and cell–microenvironment interactions of the in vivo milieu. Scaffold‐based systems integrating natural biomaterials are extensively employed in tissue engineering to improve cell survival and outgrowth, by providing the chemical and physical cues of the natural extracellular matrix (ECM). Using the freeze–drying technique, porous 3D composite scaffolds consisting of poly(3, 4‐ethylene‐dioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS), containing ECM components (i.e., collagen, hyaluronic acid, and laminin) are engineered for hosting neuronal cells. The resulting scaffolds exhibit a highly porous microstructure and good conductivity, determined by scanning electron microscopy and electrochemical impedance spectroscopy, respectively. These supports boast excellent mechanical stability and water uptake capacity, making them ideal candidates for cell infiltration. SH‐SY5Y human neuroblastoma cells show enhanced cell survival and proliferation in the presence of ECM compared to PEDOT:PSS alone. Whole‐cell patch‐clamp recordings acquired from differentiated SHSY5Y cells in the scaffolds demonstrate that ECM constituents promote neuronal differentiation in situ. These findings reinforce the usability of 3D conducting supports as engineered highly biomimetic and functional in vitro tissue‐like platforms for drug or disease modeling. Abstract : The fabrication of 3D conducting polymer scaffolds integrating extracellular matrix ‐derived proteins for hosting neuronal cell culture in vitro is reported. The composite scaffolds enhance cell survival as well as proliferation. Electrophysiology recordings performed from differentiated neurons demonstrate the contribution of extracellular matrix constituents to promote neuronal maturation in situ.